Interrelations between viral load and cellular immunity in patients with COVID-19 of varying severity - Yu. V. Nikitin; E. V. Aleksandrova; A. B. Krivoruchko; M. E. Meshkova; L. V. Minaeva; K. V. Zhdanov; A. A. Artamonov; K. V. Kozlov; A. M. Ivanov; O. V. Maltsev; K. S. Ivanov; Yu. I. Lyashenko; et al. (Медицинская иммунология, 2023)
Assessment of viral load levels in various biological samples taken from the respiratory tract can be an indicator of an ongoing process of active viral replication and may be used to monitor severe respiratory viral infections. The study of the relationship between SARS-CoV-2 viral load and immunological laboratory parameters is an important step in the search for clinical markers of COVID-19.The aim of this research was to quantify viral load in patients with COVID-19 and to identify the relation-ship between viral load and changes in the parameters of the cellular component of the immune system.A laboratory examination was carried out on 74 patients diagnosed with COVID-19, they were divided into 3 groups based on the severity of the disease: mild, moderate, severe. Total viral load in clinical samples was determined by the number of SARS-CoV-2 RNA copies per 100 copies of the reference RNaseP gene.     A comprehensive assessment of the cellular component of the immune system was performed using flow cytometry and direct monoclonal antibodies, and the IL-6, and C-reactive protein concentrations were determined.We revealed a relationship between the development of serious clinical conditions in the patients with COVID-19, and the levels of viral load. High levels of viral RNA in biological samples correlate with main indicators of the T cell component of the immune system associated with disease severity. In a subgroup of patients with an extremely high viral load, strong positive correlations were found between the relative numbers of cytotoxic lymphocytes (CD3+CD8+), activated T lymphocytes (CD3+HLA-DR+), as well as absolute and relative numbers of activated B lymphocytes and NK cells (CD3-CD25+).Laboratory monitoring of the cellular component of the immune system, along with the assessment of viral loads, should improve  early assessment of clinical condition in the patients with COVID-19. Changes   in expression levels of activation markers on immune cells can be potentially viewed as indicators of recovery during COVID-19.